Anti-Metastatic Effects on Melanoma via Intravenous Administration of Anti-NF-κB siRNA Complexed with Functional Peptide-Modified Nano-Micelles - Hisako Ibaraki; Takanori Kanazawa; Minami Owada; Keiko Iwaya; Yuuki Takashima; Yasuo Seta (MDPI AG, 2020)
Controlling metastasis is an important strategy in cancer treatment. Nanotechnology and nucleic acids with novel modalities are promising regulators of cancer metastasis. We aimed to develop a small interfering RNA (siRNA) systemic delivery and anti-metastasis system using nanotechnology. We previously reported that polyethylene glycol-polycaprolactone (PEG-PCL) and functional peptide CH2R4H2C nano-micelle (MPEG-PCL-CH2R4H2C) has high siRNA silencing effects, indicated by increased drug accumulation in tumor-bearing mice, and has an anti-tumor effect on solid tumors upon systemic injection. In this study, we aimed to apply our micelles to inhibit metastasis and evaluated the inhibitory effect of anti-RelA siRNA (siRelA), which is a subunit of NF-κB conjugated with MPEG-PCL-CH2R4H2C, via systemic administration. We report that siRelA/MPEG-PCL-CH2R4H2C had a high cellular uptake and suppressed the migration/invasion of cells in B16F10 cells without toxicity. In addition, in a lung metastasis mouse model using intravenous administration of B16F10 cells treated with siRelA/MPEG-PCL-CH2R4H2C, the number of lung nodules in lung tissue significantly decreased compared to naked siRelA and siControl/MPEG-PCL-CH2R4H2C micelle treatments. Hence, we show that RelA expression can reduce cancer metastasis, and MPEG-PCL-CH2R4H2C is an effective siRNA carrier for anti-metastasis cancer therapies.